2021
DOI: 10.1021/acssuschemeng.1c06741
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive, Stretchable, and Sustainable Conductive Cellulose Nanocrystal Composite for Human Motion Detection

Abstract: Sensitive strain sensors (an important component of soft robotics, wearable devices, and biomedical electronics) with high sensitivity, stretchability, and long-term stability are still challenging. A sensitive, stretchable, and sustainable sensor using poly­(3,4-ethylenedioxythiophene) (PEDOT) coated cellulose nanocrystals (CNC) with poly­(vinyl alcohol)/glycerol (PVA/Gly) composite is proposed. The low cost and sustainable PEDOT coated CNC with high aspect ratio lowered the electrical percolation threshold t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The GF values of CGM/EGaIn films were 31.09, 63.46, and 663.98 during the strain range of 0–2%, 2–4%, and 4–5%, respectively, indicating CGM/EGaIn films exhibited an ultrahigh strain sensitivity at the small strain. Figure e showed that the sensitivity of CGM/EGaIn films was much higher than most of the reported biomass-based sensors. Therefore, the human motion (such as throat vibrating (Figure f), wrist bending (Figure g) and finger bending (Figure h)) manners can be easily monitored by recording the obvious and regular relative resistance changes of CGM/EGaIn-50% film in a repeatable bending manner.…”
Section: Results and Discussionmentioning
confidence: 91%
“…The GF values of CGM/EGaIn films were 31.09, 63.46, and 663.98 during the strain range of 0–2%, 2–4%, and 4–5%, respectively, indicating CGM/EGaIn films exhibited an ultrahigh strain sensitivity at the small strain. Figure e showed that the sensitivity of CGM/EGaIn films was much higher than most of the reported biomass-based sensors. Therefore, the human motion (such as throat vibrating (Figure f), wrist bending (Figure g) and finger bending (Figure h)) manners can be easily monitored by recording the obvious and regular relative resistance changes of CGM/EGaIn-50% film in a repeatable bending manner.…”
Section: Results and Discussionmentioning
confidence: 91%
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Resistive sensors generally have a faster response time. Lee et al 252 prepared a sensitive, stretchable, and sustainable conductive cellulose nanocrystal composite for human motion detection (Fig. 18a).…”
Section: Applicationsmentioning
confidence: 99%